TINGKAT PRODUKTIVITAS TENAGA KERJA SEKTOR PERTANIAN DI PROVINSI SULAWESI UTARA - Ratih M. Amin; Oktavianus Porajouw; Charles R. Ngangi; Yolanda P.I. Rori (Universitas Sam Ratulangi, 2014)
ABSTRACTRatih Mawarni Amin, Level of Labor Productivity of Agriculture Sector in North Sulawesi Province. (Underguidance of Oktavianus Porajow as a Chairman, Charles R. Ngangi and Yolanda P, I Rori as members).The objective this research is to determine the level of labor productivity in the agricultural sector in North Sulawesi. This research was conducted for three months starting from July 2014 until September 2014 in the North Sulawesi Province. The source data used secondary data obtained from agencies associated with this research that the Central Bureau of Statistics in North Sulawesi Province. This analysis used descriptive analysis and the ratio between Gross Domestic Product (GDP) and the amount of labor.The results of this study showed that labor productivity in the agricultural sector of the North Sulawesi in 2012 was 12.11 million rupiah / worker, compared with 2008 which only amounted to 8.94 million rupiah / worker. Productivity of labor was likely to increase from 2008 through 2012.